A worthy conservation target? Revising the status of the rarest bumblebee of Europe. Issue 5 (24th May 2021) - Ghisbain, Guillaume; Martinet, Baptiste; Wood, Thomas J.; Przybyla, Kimberly; Cejas, Diego; Gérard, Maxence; Rasmont, Pierre; Monfared, Alireza; Valterová, Irena; Michez, Denis
Abstract: Against the context of global wildlife declines, targeted mitigation strategies have become critical to preserve what remains of biodiversity. However, the effective development of conservation tools in order to counteract these changes relies on unambiguous taxonomic determination and delineation. In this study, we focus on an endemic bumblebee species recorded only from the highest altitudes of the Sierra Nevada (Spain), Bombus reinigiellus (Rasmont, 1983). The species has the smallest range of any European bumblebee, along with a restricted diet and an inability to disperse because of its isolated montane distribution, making it an appropriate conservation target. However, through an integrative taxonomic approach including genetics, morphometrics and semio‐chemistry, we demonstrate the conspecificity of this taxon with one of the most common and widespread bumblebee species of Europe, Bombus hortorum (L. 1761). We assign a subspecies status to this endemic taxon ( Bombus hortorum reinigiellus comb. nov. ) shown to be different in colour and morphology but also in wing shape and relative wing size compared to the other conspecific subspecies. Following our taxonomic revision, we reassessed the IUCN conservation status of Bombus hortorum both at the continental and Spanish scale. We then propose how historic climatic oscillations of the last Ice age could explain such a phenotypic divergence in a post‐glacial refugium and highlight the critical role of establishing unambiguous taxonomic revision prior to any conservation assessment. Abstract : We carried out an integrative taxonomic analysis on an endemic bumblebee species recorded only from the highest altitudes of the Sierra Nevada (Spain), Bombus reinigiellus, known as the rarest bumblebee of Europe. We demonstrate the conspecificity of this taxon with one of the most common and widespread bumblebee species of Europe, Bombus hortorum . We reassessed the IUCN conservation status of Bombus hortorum and propose discuss how historic climatic oscillations of the last Ice age could explain such a phenotypic divergence of the taxon reinigiellus in a post‐glacial refugium.